Call Setup over VoIP in Softswitch System using Web Interface and Application - Jamaludin, Mohamad Haikal; Anuar, Abul Khair (Evolution in Electrical and Electronic Engineering, 2022)
PThe telephone network has enabled long-distance communication between two people which was previously impossible. As the telephone technology grows, phone calls no longer require a dedicated physical circuit which has now been replaced with VoIP which converts phone calls to internet data. Softswitch system uses a web interface and application is used to set up call over VoIP in many governments and non-government telephone exchange systems. In this work, call setup using Green Packet Global's telecom architecture and Wireshark as a network packet analyser were investigated. A descriptive study and inferential analysis utilising a Wilcoxon signed-rank test were used to establish network traffic dependability and responsiveness with 16 Call ID samples. Local and international network traffic varies slightly in RTP packets, mean jitter, and timestamping. A descriptive examination of RTP packets found 99 percent local and international packet delivery success. Using inferential analysis to analyse mean jitter and timestamping, it was found that 95 percent of call quality was maintained in terms of mean jitter and online record keeping. The measurement result showed that the company's call setup meets its standards. In contrast, the network company's Service Level Agreement (SLA) is similar to other organisations without any server or network difficulties.